Direct torque control of AC motors using FPGA programming II - Kang, Wei Rong (2014)
Today, there are many industrial applications which require high performance electrical drives. For example, the direct torque control (DTC) drive from ABB boasts a switching frequency of 40 kHz. To achieve this, a Digital Signal Processor (DSP) with fast computational capabilities is essential. A high switching frequency places a lot of computational burden on the DSP and it is often not realisable even with modern DSPs.